On Veblenian Waste and Polanyian Protective Responses: Evidence from the US - Wrenn, Mary V. (Panoeconomicus, 2018)
As capitalism unfolds, continual technological advance in combination with the relentless accumulation imperative serves to amplify material progress. The institutionalization of the market fundamentally changes the structure of society and the institutional structure through which individuals are socialized; the socialization process becomes increasingly accommodating to the intensifying marketplace. The social dislocation generated by the intensification of the market, prompts Polanyi’s protective response. Despite this intensification of the market setting, the existence of the economic surplus fund undermines the syllogistics of market determined pricing. Evidence of the economic surplus and that the competitive law of value is not operable within monopoly capitalism is found in the thriving lobby industry and generous campaign contributions. This research seeks to connect explicitly the concepts of Polanyi’s protective response with Veblenian waste and the economic surplus in order to better understand how the irrational system of neoliberalism continues to evolve. Key words: Veblen, Polanyi, Economic surplus, Neoliberalism, Monopoly capitalism. JEL: B52, N32, P10, Z10.